Towards a Bipolar World. Book Review of ‘The Second World War and the Transformation of International Relations: From Multipolarity to a Bipolar World’ edited by L.S. Belousov and A.S. Manykin - V. I. Batyuk (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In 2020 the whole world commemorated the 75th anniversary of the end of World War II — the most horrifi c war in the human history. However, the celebration of the victory over fascism was overshadowed by the growing tension among the leading actors of contemporary international relations. In this context, a high level of responsibility falls on the academic community to rebuff politically motivated attempts to rewrite history and revise the outcomes of this war. The book under review could make an important contribution to that end. The book provides a comprehensive and balanced analysis of the history of World War II. The reviewer emphasizes that rather than providing a detailed examination of military operations the authors focused on their impact on the development of the international relations system. In particular, the book provides a detailed picture of the complex interactions within the strategic triangle — the Soviet Union, the United States, and Great Britain — both during the war and in the years after the war. As a result, the book under review not only provides an opportunity to better understand the key trends in relationships between the Great Powers during the war, but also sheds new light on the origins of the bipolar system and the beginning of the Cold War. The reviewer concludes that, despite sometimes excessively Eurocentric approach of the authors, this book is a seminal work on the history of World War II and a major event for the Russian academic community. As such, this book can be recommended to both professional historians and a wider audience.